1999
DOI: 10.1161/01.cir.100.19.1964
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognostic Value of Rest-Redistribution 201 Tl Single-Photon Emission Computed Tomography

Abstract: Background-The incremental prognostic value of rest-redistribution 201 Tl compared with stress and rest perfusion abnormalities has not been defined. Methods and Results-We identified 458 patients who underwent rest 201 Tl /stress (exercise or adenosine) 99m Tc sestamibi single-photon emission computed tomography (SPECT) and had late (18 to 24 hours) 201 Tl imaging, were not revascularized within 60 days of SPECT, and were followed up at Ͼ1 year. SPECT images were visually analyzed with the use of a 20-segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…With respect to the prognostic complementarity of LGE and perfusion, the authors found that reversible perfusion defects and the presence of LGE were both associated with the end point of CD/MI in both univariate analyses and after adjustment for patient sex and age in a model inclusive of both of these CMR variables. This finding extends results from previous studies reporting the complementary nature of stress perfusion and viability 7 to CMR, justifying the acquisition and reporting of both of these data elements.…”
Section: Article See P 1390supporting
confidence: 88%
“…With respect to the prognostic complementarity of LGE and perfusion, the authors found that reversible perfusion defects and the presence of LGE were both associated with the end point of CD/MI in both univariate analyses and after adjustment for patient sex and age in a model inclusive of both of these CMR variables. This finding extends results from previous studies reporting the complementary nature of stress perfusion and viability 7 to CMR, justifying the acquisition and reporting of both of these data elements.…”
Section: Article See P 1390supporting
confidence: 88%
“…Although single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) has been shown to identify patients at high risk of cardiovascular events and cardiovascular mortality, [11][12][13] including those resuscitated from SCD, 14 it remains unknown whether it can identify patients with CAD at risk for de novo SCD. The goal of this study is to determine whether SPECT MPI can identify patients with CAD at increased risk of SCD.…”
Section: Editorial See P 175 Clinical Perspective See P 188mentioning
confidence: 99%
“…Recent data by Hachamovitch et al 25 also demonstrated an increasing event rate that paralleled the increasing abnormalities on perfusion imaging. In addition, Sharir et al 26 have recently emphasized again the strong prognostic value of LVEF (in that study derived from gated SPECT data).…”
Section: Ischemia Viability and Scar Tissue Versus Treatment And Prmentioning
confidence: 86%